Prevalence and healthcare costs associated with the management of diabetic foot ulcer in patients attending Ahmadu Bello University Teaching Hospital, Nigeria - Danmusa, Umar Mukhtar; Terhile, Iorliam; Nasir, Idris Abdullahi; Ahmad, Auwal Alkasim; Muhammad, Habiba Yahaya (International Journal of Health Sciences, 2016)
Introduction: Diabetic foot ulcers (DFU) are non-traumatic lesions of the skin on feet of diabetic patients. DFU require appropriate investigations, dietary placement and clinical management. These constitute huge healthcare costs in DFU care. Objective: This study sought to determine the prevalence of DFU in relation to clinical, sociodemographic variables and healthcare costs expended. Methods: This was a retrospective study. Hence, medical records and healthcare costs of 1573 DFU-diagnosed patients who visited the diabetic clinic and medical wards of Ahmadu Bello University Teaching Hospital, Nigeria were reviewed and analyzed for relevant data. Results: The prevalence of DFU in patients with diabetic mellitus (DM) was 6.0% with more cases in men (67.2%) than women (32.8%). The prevalence of DFU in relation to type of DM was 6.5% and 0% for DM type-II and DM type-I respectively. The distribution of DFU in relation to clinical stages was 40%, 25.7%, 17.1% and 11.4% for stages-IV, III, II and I. Patients in the age group 51-60 years had the highest frequency of DFU (28.6%), but there was no DFU in those 10-20 years and > 80 years. It required an average of 1808 US to successfully treat patients with DFU stage IV, while 1104 US and 556 US was required to treat DFU stage III and II respectively. Cost of procuring drugs covered the highest burden of total healthcare cost in managing DFU (35%-46%). Conclusion: The prevalence of DFU in DM patients attending ABUTH was high. Healthcare costs associated with DFU especially cost of drugs procurement contributed the highest financial burden in managing DFU. Keywords: Diabetic mellitus, Diabetic foot ulcer, Financial costs, Chemotherapy, Nigeria.